IMPROVING STUDENTS™ ACHIEVEMENT IN READING NARRATIVE TEXT BY USING RECIPROCAL TEACHING METHOD - Sianturi, Ruth Adelina (Universitas Negeri Medan, 2014)
Abstract This study deals with the improving students™ achievement in reading narrative text by using reciprocal teaching. The research of this study was conducted by using action research. The subject of this study was the tenth grade students SMA Negeri 6 Medan. One class was taken as the subject, namely the students from X-5. There were 49 students, consisting of 22 male and 27 female. This research was done in two cycles; there was three meetings in cycle I and three meetings in cycle II. The instruments for collecting data were reading narrative text (25 items of multiple choice tests) teacher make test as quantitative data and interview sheet, observation sheet and diary notes as qualitative data. In analyzing the data, the mean of the students™ score for the treatment I was 61.79, for the treatment II was 72.24 and treatment III was 81.71. The data showed that the students™ score was rising in every treatment. The conclusion is that the use of reciprocal teaching method can improve students™ reading comprehension in narrative text. It suggested to English teacher to apply reciprocal teaching method in teaching reading comprehension. Key words: reading, narrative text, reciprocal teaching.